The Influence of Risk Perception, Trust, and Perceived Benefits and The Decision to Use QRIS in MSMEs in Bangli Regency - Pande Putu Suryawati; Ade Maharini Adiandari; Bagus Arya Wijaya (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Technological advances have brought digital payment innovations such as QRIS that provide efficiency for Micro, Small, and Medium Enterprises (MSMEs). However, in Bangli Regency, the level of use of QRIS in buying and selling transactions and other transactions. is still the lowest compared to other areas in Bali. This study aims to analyze the influence of Perception of Trust Risk and Perception of Benefits on the Decision to Use QRIS simultaneously and partially in MSMEs in Bangli Regency. The research method is associative with a quantitative approach. The population used in this study is all MSMEs in Bangli Regency that have not used the QRIS digital payment method, which is as many as 340 MSMEs. The sample was determined using the random sampling method, so that 77 respondents were obtained as samples. Using data analysis methods are multiple linear regression analysis, determination analysis, t-test (partial), and f-test (simultaneous) using SPSS 25 software. The results of the study show that simultaneously Risk Perception, Trust, and Benefit Perception have a significant effect on the decision to use QRIS. Partially, Risk Perception has a significant negative effect, while Trust and Benefit Perception have a significant positive effect on the decision to use QRIS in MSMEs in Bangli Regency.